Ex Situ Liver Machine Perfusion: The Impact of Fresh Frozen Plasma. Issue 2 (21st January 2020) - Liu, Qiang; Hassan, Ahmed; Pezzati, Daniele; Soliman, Basem; Lomaglio, Laura; Grady, Patrick; Del Angel Diaz, Laurent; Simioni, Andrea; Maikhor, Shana; Etterling, John; D'Amico, Giuseppe; Iuppa, Giuseppe; et al.
Abstract : The primary aim of this single‐center, phase 1 exploratory study was to investigate the safety, feasibility, and impact on intrahepatic hemodynamics of a fresh frozen plasma (FFP)–based perfusate in ex situ liver normothermic machine perfusion (NMP) preservation. Using an institutionally developed perfusion device, 21 livers (13 donations after brain death and 8 donations after circulatory death) were perfused for 3 hours 21 minutes to 7 hours 52 minutes and successfully transplanted. Outcomes were compared in a 1:4 ratio to historical control patients matched according to donor and recipient characteristics and preservation time. Perfused livers presented a very low resistance state with high flow during ex situ perfusion (arterial and portal flows 340 ± 150 and 890 ± 70 mL/minute/kg liver, respectively). This hemodynamic state was maintained even after reperfusion as demonstrated by higher arterial flow observed in the NMP group compared with control patients (220 ± 120 versus 160 ± 80 mL/minute/kg liver, P  = 0.03). The early allograft dysfunction (EAD) rate, peak alanine aminotransferase (ALT), and peak aspartate aminotransferase (AST) levels within 7 days after transplantation were lower in the NMP group compared with the control patients (EAD 19% versus 46%, P  = 0.02; peak ALT 363 ± 318 versus 1021 ± 999 U/L, P  = 0.001; peak AST 1357 ± 1492 versus 2615 ± 2541 U/L, P  = 0.001 of the NMP and control groups, respectively). No patient developed ischemic type biliary stricture. One patient died, and all other patients are alive and well at a follow‐up of 12‐35 months. No device‐related adverse events were recorded. In conclusion, with this study, we showed that ex situ NMP of human livers can be performed safely and effectively using a noncommercial device and an FFP‐based preservation solution. Future studies should further investigate the impact of an FFP‐based perfusion solution on liver hemodynamics during ex situ normothermic machine preservation.